Evaluation of Kangkong (Ipomoea aquatic L.) genotype, a potential green leafy vegetable in summer season at Khajura, Banke, Nepal - Lohani, S.; Shrestha, S. L.; Rawal, R.; K.C., Y.; Aryal, L. N. (Journal of Agriculture and Forestry University, 2022)
Kangkong (Ipomoea aquatica L.) belongs to the plant family Convolvulaceae. A set of varietal trial was conducted in Directorate of Agricultural Research Khajura, Banke, Nepal with three genotypes; HRDKAN001 (Combodian), HRDKAN002 (Thaipalungo as check variety) and HRDKAN003 (Bangladeshi); which were collected through National Horticulture Research Centre, Khumaltar. The objectives of this experiment were to select high yielding genotypes for green leaf production during summer season. The experiments were carried out in two consecutive years, April 2017 and 2018 and laid out in Randomized completely block design with seven replications in open field condition. The spacing was maintained 50 cm row to row and 30 cm within the row in each year. Plants were fertilized with 200:150:120 kg NPK and 20 tons farm-yard manure per hectare. Data were recorded on vegetative growth, disease response, vegetative yield, qualitative parameter and consumer’s preference. From the result of experiment, HRDKAN001 and HRDKAN002 were found to be higher yielding and showed good cooking quality and these genotypes were selected for the further evaluation at Khajura and similar agro-ecological conditions of Nepal.